Modelling invasive pathogen load from non-destructive sampling data - Martínková, Natália; Škrabánek, Pavel; Pikula, Jiri (Journal of theoretical biology, 2019)
Where microbes colonizing skin surface may help maintain organism homeostasis, those that invade living skin layers cause disease. In bats, white-nose syndrome is a fungal skin infection that affects animals during hibernation and may lead to mortality in severe cases. Here, we inferred the amount of fungus that had invaded skin tissue of diseased animals. We used simulations to estimate the unobserved disease severity in a non-lethal wing punch biopsy and to relate the simulated pathology to the measured fungal load in paired biopsies. We found that a single white-nose syndrome skin lesion packed with spores and hyphae of the causative agent, Pseudogymnoascus destructans, contains 48.93 pg of the pathogen DNA, which amounts to about 1560 P destructans genomes in one skin lesion. Relating the information to the known UV fluorescence in Nearctic and Palearctic bats shows that Nearctic bats carry about 1.7 µg of fungal DNA per cm2, whereas Palearctic bats have 0.04 µg cm-2 of P. destructans DNA. With the information on the fungal load that had invaded the host skin, the researchers can now calculate disease severity as a function of invasive fungal growth using non-destructive UV light transillumination of each bat's wing membranes. Our results will enable and promote thorough disease severity assessment in protected bat species without the need for extensive animal and laboratory labor sacrifices.
Keywords: Wings, Animal; hibernace; Chiroptera; křídla zvířecí; dermatomykózy; Dermatomycoses; kůže; Bat; ultrafialové záření; Animals; Skin; zvířata; Hibernation; Ultraviolet Rays; Ascomycota; Fungal infection; Skin lesion; Pathogen load; White-nose syndrome; Pseudogymnoascus destructans; UV light diagnostics